Barriers of PMTCT (Prevention Mother to Child Transmission) Program: Systematic Review - Miftah Chairunnisa (Jurnal Ners dan Kebidanan, 2020)
HIV infection during pregnancy is a serious problem that requires special attention because the number of case increasing every year. According to UNAIDS data, more than 36.9 million people were living with HIV on 2017. An increase of 1.8 million new cases and 940,000 deaths occurs in the same year. In Indonesia especially, there were about 630,000 HIV cases on 2017 and nearly 49,000 new cases reported. This number consists of cases of vertical transmission from mother to child during pregnancy. The government has implemented PMTCT (Prevention Mother to Child Transmission) program as a solution to reduce the number of HIV cases. Nevertheless this program has not been running well due to several barriers regarding to its implementation. This study aimed to provide an understanding of various barriers to PMTCT program implementation. A systematic review approach by PRISMA design was used to study literatures from databases. Stigma or discrimination from community and health care, experienced by HIV patients, was major barrier that impede PMTCT program. In addition, lack of support from partner or family, depression, economic factors, stigma from health workers, and health workers’ income-workload discrepancy were also significantly affected the implementation. Contrary, the active role of health workers to provide counseling and education about HIV/AIDS among community as well as to client’s families was a success key of PMTCT program.